Indonesia : archipelago of fear - Vltchek, Andre (Pluto Press, 2012)
This volume is a fascinating and at times unsettling journey into the world's most populous Muslim nation as it struggles to emerge from decades of dictatorship and the plunder of its natural resources. Andre Vltchek brings together more than a decade of investigative journalism in and around Indonesia to chart its recent history.